Use of geospatial tools in morphometric analysis and prioritisation of sub-catchments of the soundgrougrou (Casamance Basin) - Faye, Cheikh; Ndiaye, Modou (Quaestiones Geographicae, 2021)
The prioritisation of catchments, particularly in the context of catchment plans and management programmes, is part of water resources development. In fact, morphometric analysis assisted by geospatial technology is carried out by prioritising sub-catchments according to their natural resource availability characteristics. Information on the geomorphology and erosion factors of the study area is used in the area in the preparation of local models of ungauged sub-catchments, which otherwise lack an adequate hydrological database. The objective of this paper is to use geographic information systems (GISs) in morphometric analysis to prioritise sub-catchments of the Soungrougrou (a tributary of the Casamance River). In this respect, the integrated methodology involving morphometric aspects from geospatial technology is used. To carry out the geospatial research, basic mathematical equations used in a GIS environment were used to measure a series of aspects of hydrology such as flow length, flow length ratio, bifurcation ratio, drainage density, drainage texture, flow frequency, elongation rate, circularity ratio, form factor, relief and relief ratio. The results divided the whole catchment into three priority areas, namely high, medium and low. The results are relevant for establishing soil and water conservation plans in the Soungrougrou basin, as well as adequate groundwater production and management. The high category (sub-basins 6, 8, 14, 17 and 18) is subject to maximum soil erosion, which requires immediate intervention to avoid possible natural hazards.